Restorative Justice and Hybrid Mediation: Reforming Civil Dispute Resolution in Indonesian Courts - Jeremiah Ray Wilson; Adi Sulistiyono (Yayasan Cerdas Pedia Indonesia, 2026)
This article evaluates the effectiveness of mediation processes in Indonesian civil dispute resolution, emphasizing restorative justice and institutional challenges. By employing a normative empirical methodology, the study analyzes Supreme Court data and Scopus indexed literature to assess systemic disparities between religious and general courts. Findings demonstrate a steady increase in mediation success, reaching fifty four percent recently. However, this success is severely hindered by overreliance on external mediators who often lack substantive legal authority, alongside cultural tendencies favoring adversarial litigation. The novelty of this research lies in proposing a hybrid mediation model and institutionalizing customary restorative justice principles within civil procedures to fulfill substantive justice. The study concludes that mandatory certification, advanced digital mediation platforms, and continuous cross sectoral collaboration are strictly essential. Ultimately, optimizing these structural frameworks will significantly reduce case backlogs, ensuring that amicable settlements become the fundamental pillar of a sustainable and highly equitable modern judicial system.